2019
DOI: 10.1111/bcpt.13279
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits Aβ25‐35‐induced apoptotic cell death in SH‐SY5Y cells

Abstract: Metformin, a first-line drug for type-2 diabetes, plays a potentially protective role in preventing Alzheimer's disease (AD), but its underlying mechanism is unclear. In this study, Aβ 25-35 -treated SH-SY5Y cells were used as a cell model of AD to investigate the neuroprotective effect of metformin, as well as its underlying mechanisms.We found that metformin decreased the cell apoptosis rate and death, ratio of Bcl-2/ Bax, and expression of NR2A and NR2B, and increased the expression of LC3 in Aβ 25-35 -trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…Metformin decreases the apoptosis of Aβ-treated SH-SY5Y neuroblastoma cells by repressing the intracellular concentration of Ca 2+ and ROS generation. Moreover, metformin enhances the autophagy process by promoting the conversion of microtubule-associated protein 1 light chain 3 (LC3) in neuroblastoma cells (Li et al, 2019). Underexposure to Aβ, the primary cultured rat hippocampal neurons have substantial neuronal death.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Metformin decreases the apoptosis of Aβ-treated SH-SY5Y neuroblastoma cells by repressing the intracellular concentration of Ca 2+ and ROS generation. Moreover, metformin enhances the autophagy process by promoting the conversion of microtubule-associated protein 1 light chain 3 (LC3) in neuroblastoma cells (Li et al, 2019). Underexposure to Aβ, the primary cultured rat hippocampal neurons have substantial neuronal death.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…The present findings suggest that miR-33 interference strikingly inhibits activation of the Akt/mTOR signal pathway and upregulates autophagy. Oxidative stress, inflammation, and the endogenous caspase apoptosis pathway have been implicated in Ab neurotoxicity [6,26]. In this study, we uncovered the role of miR-33 in apoptosis, inflammation, and oxidative stress of neurons.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that aggregated and accumulated Ab peptides can bring about hyperphosphorylation of tau protein and neurofibrillary tangles [5]. Evidence suggests that multiple factors, including apoptosis, inflammation, and oxidative stress, contribute to AD [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the cell toxicity of Aβ 25-35 peptide (10–30 µM) in PC12 and SH-SY5Y cells ( 30 32 ). Our previous study demonstrated that treatment with Aβ 25-35 peptide (10–30 µM) alone reduced the cell viability at 24, 48 and 72 h ( 22 ).…”
Section: Resultsmentioning
confidence: 99%